A produção social e tecnológica do trabalho (in)formal na rede de reciclagem no estado do Rio de Janeiro - Uilmer Rodrigues Xavier da Cruz (2024)
This thesis aims to investigate the social and technological production of collection in recycling networks, with emphasis on the Recycling Network of the State of Rio de Janeiro (RRERJ), chosen as a paradigmatic case. This choice is due to the plurality of subjects that make up the RRERJ and the relationships that these subjects establish with each other. It starts from the hypothesis that recycling networks work according to the logic of capitalism, reproducing, in the informal economy, the same modus operandi of the formal economy, but without the same guarantees. It is observed that the collecting activity, although it plays an important role in the environment, feeds a mode of production that ends up validating the exploitation and exclusion of the worker, contributing to the maintenance of the game of unequal forces, in which some take advantage of the surplus labor of others. In this sense, the focus is placed on technological production, understood as that which includes the products and technological processes used with the purpose of solving social problems of a practical nature, as a way of deconstructing old paradigms and establishing new ones, through which it is possible to develop a new perspective on the work and the waste pickers. It is believed that, in addition to its banal application, which aims to bring comfort to human life, technology can serve to make the masses aware of the problem of waste production and of the importance of those who, in some way, treat this symptom of capitalism. In this sense, two new disruptive technologies will be presented, used experimentally in cultural events, that reveal great potential for impact. This thesis is organized into five chapters, corresponding to articles already published in nationally and internationally renowned journals. The first chapter addresses labor relations derived from the rise of capitalism in the modern world, making use of two valuable concepts for the proposed analysis: formal work and informal work, coined by Marx and Engels. The second chapter focuses on the relationship between the collector and the recycling industry, showing how the latter reinforces the capitalist discourse through the relationship of domination that is nurtured by the collector worker. The third chapter, in turn, addresses this relationship from the notion of space, facing geographic studies. In the fourth chapter, the discussion on technological production begins, through the notion of sustainability. This discussion continues in the next chapter, which develops the knowledge economy seeking to understand how knowledge, experience and innovations can contribute to the improvement of processes and work in industries such as recycling. Finally, the last chapter, which deals with green patents, presents the two aforementioned technologies, which, as mentioned, represent possibilities for a paradigm shift: the change is capable of favoring the waste pickers and their work, demonstrating that, even if they are on the sidelines, they have a central role and function in a world where more and more waste is produced.